If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 5(2x + 1) + -3(2x + -3) Reorder the terms: 0 = 5(1 + 2x) + -3(2x + -3) 0 = (1 * 5 + 2x * 5) + -3(2x + -3) 0 = (5 + 10x) + -3(2x + -3) Reorder the terms: 0 = 5 + 10x + -3(-3 + 2x) 0 = 5 + 10x + (-3 * -3 + 2x * -3) 0 = 5 + 10x + (9 + -6x) Reorder the terms: 0 = 5 + 9 + 10x + -6x Combine like terms: 5 + 9 = 14 0 = 14 + 10x + -6x Combine like terms: 10x + -6x = 4x 0 = 14 + 4x Solving 0 = 14 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 0 + -4x = 14 + 4x + -4x Remove the zero: -4x = 14 + 4x + -4x Combine like terms: 4x + -4x = 0 -4x = 14 + 0 -4x = 14 Divide each side by '-4'. x = -3.5 Simplifying x = -3.5
| x^3+2x^2+7x+3ifx=10 | | -17-11z=104 | | 6x-12=-2x | | 60=4w+12 | | -2n=6-n | | 4(y+3)+8=80 | | 4(7x-4)+3(13-4x)-3(5x+5)=-3 | | 24k+15= | | 7(x+6)=6(x-3) | | 3x-11=10x+12 | | x-(x*0.25)-(x*0.3399)=50000 | | 0=16t^2-300t+2000 | | 21d^2-7d=O | | 6x+4y-2x+5y-5x= | | 12x^3-12x-45=0 | | x+.03x=23.6 | | t(n)=4n-2 | | 7(n-1)=-(3+n) | | k^2+5k-9=0 | | y=-1x^2+29x+12 | | 4r-10= | | 770=3x+77 | | x^2+x=-c | | 5.2+1.7n=1.12 | | 2m+k+3m+2k= | | k+1=k^2+k+c | | 3w+14=50 | | k=-2k^2-k | | 8x+7=5x-21 | | 3(p+4)=24 | | 4y+6y-5=10y-5 | | 5k+40L-35m= |